The Content of the Process for Forming the Concepts of Tolerance in Primary Class Students - Mohammad, Dehkanbayev (Jurnal Pendidikan Non formal, 2024)
In this article, the content of the concept of tolerance and the essence of the processes aimed at forming the concept of tolerance in primary classes are reflected in the article. This article examines the pivotal role of tolerance in the multi-ethnic society of Uzbekistan, emphasizing its relevance in mitigating conflicts arising from diverse cultural values. This article draws on a combination of qualitative and descriptive methods, integrating historical and cultural contexts to analyze the evolution of tolerance concepts. This article concludes by underscoring the transformative power of tolerance in fostering resilience and internationality, drawing inspiration from the enduring examples of the Uzbek people.